(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research article aims to propose the model of integrated Buddhist social development based on Buddhist (Three-Fold Principle) participation. The research methodology applied documentary research consisting of in-depth interviews from key informants, in terms of focus group data. The process of action research was also used to achieve empirical results with descriptive analysis technique. The research result revealed that the model of integrated Buddhist social development based on Buddhist (Three-Fold Principle) participation enabled social members, when applied, to gain ‘Right View, Right Thought, Right Speech, Right Action, Right Livelihood, Right Effort, Right Mindfulness, and Right Concentration.” As well, they would be developed in 3 manners: • They became social members of pertaining morality, maintaining morality called training in higher morality. What existed in their society presented the members’ morality and cultural elevation; i.e., driving to attain the Five Precepts practice. • They became social members of being volunteering, public-minded from mental development training among themselves. These helped to establish strength and peace in their society; i.e., after training mental discipline. • They became social members of wise called being trained in higher wisdom. Also, from being trained in welfare education to attain the Right View and the Right Thought, people would become comprehend completely in cause and reason, in right and wrong, in suitability and unsuitability, in cause and effect, in knowingly, and in matter relationship.